Marital disputes: mediation as an alternative to litigation / Muhammad Hisyam Abdullah, Aida Natasha Abdul Rahman and Ahmad Fuad Hasim. - Abdullah, Muhammad Hisyam; Abdul Rahman, Aida Natasha; Hasim, Ahmad Fuad (2008)
The topic of this research is Marital Disputes; Mediation as an Alternative to Litigation. Alternative disputes resolutions has existed since time in memorial, used by ancient civilizations to settle disputes prior to the establishment of the legal system. However, the scenario as it is now shows how alternative dispute resolution is not as popular as it used to be. This research will give a glimpse on the problems with regards to marital disputes arising from the use of litigation as a mean to solve problems, and how mediation as its alternative could cater to those problems. This research will not only focus on the civil position, but also the position under the Syariah law in Malaysia.